Analysis and Design of Online Sales Informationsystems (e-Commerce) At Seventeen tembilahan Using Descriptive Analysis: Analysis and Design of Online Sales Informationsystems (e-Commerce) At Seventeen tembilahan Using Descriptive Analysis - Dwi Yuli Prasetyo; Asniati Bindas (Indragiri Islamic University, 2023)
In this ever-evolving age, all needs can be met quickly and easily thanks to technology. For example, in the past if we wanted to buy an item or product, such as clothes, we had to come directly to the seller or shops that were open. We no longer need to be complicated by the existence of increasingly sophisticated and modern technology today because now there are shops that offer the goods we need via the internet, namely through e-Commerce or also known as online stores. The author wants to create an online sales information system that can sell daily necessities quickly and efficiently because Toko Seventeen Tembilahan is a shoe shop, clothes, pants and so on that sells goods but still uses a manual system. The design of this application will be made using descriptive analysis and the system will be made in stages, starting from analysis, system design, system creation, implementation, and maintenance. The purpose of this application is to help the community by no longer needing to visit the location directly to buy the goods or products they want and to help Toko Seventeen sell and promote their goods or products quickly without space and time limits. Keywords: website, seventeen, e-commerce, tembilahan